A new species of brachycephalus (anura: Brachycephalidae) from the highlands of the atlantic forest, Southeastern Brazil - Condez, Thais H. [UNESP]; Clemente-Carvalho, Rute B. G.; Haddad, Célio F. B. [UNESP]; Dos Reis, Sergio F. (Herpetologists League, 2014)
A new species of brachycephalid frog is described from the highlands of the Atlantic Forest in Serra do Mar, municipality of Cunha, São Paulo State, southeastern Brazil. Specimens were collected amidst the leaf litter at approximately 920 m above sea level. The new species is distinguished from all of its congeners by the combination of the following characters: snout-vent length 9.5-15.6 mm; rough dorsum; general background color orange with a variable density of whitish spots on dorsum; skin on head and dorsum granular with dermal ossification; skull, spinal processes of sacral and presacral vertebrae, and process of the fourth vertebra hyperossified; absence of hyperossification in the central portion of the skull; dorsal surface of body covered by osteoderms. The new species was found active by day and is locally abundant. Males hold territories during the reproductive season. Females had few mature oocytes during the same period. The advertisement call of B. crispus is a long and low-intensity buzz with a regular repetition of notes.
Keywords: Advertisement call; Atlantic rainforest; Cunha; Direct-developing frog